In vitro evaluation of virulence factors associated with clinical isolates of Candida species from patient in tertiary care hospital in Central India - Dr Jyoti Gupta; Dr. Harshada Shah (Tropical Journal of Pathology and Microbiology, 1970)
Background: Adherence to host tissues, morphological changes and secretion of extracellular hydrolytic enzymes are important virulence attributes of Candida species. These enzymes play pivotal roles in pathogenicity of Candida infection.Aim: The present study was conducted with an aim to determine in vitro phospholipase, haemolysin, Coagulase activities and biofilm production of Candida species isolated from various Clinical samples.Material and Method: A total of 156 Candida species isolated from various clinical specimens were identified up to species level by standard mycological techniques and was tested for extracellular hydrolytic enzyme activity and Biofilm formation.Results: 156 Candida species were isolated from 915 clinical specimens. Biofilm production was shown by 77 candidal strains (49.35%), phospholipase activity was observed by 74 candidal strains (47.43%). haemolysin activity was observed by 66 candidal strains (42.30%) and Coagulase production in 38 of Candida (24.35%) isolates.Conclusion: Both C. albicans and Non-albicans Candida (NAC) species produce extracellular hydrolytic enzymes. Since these enzymes are important to understand the co-relation between the species and infection, their detection is extremely important in the management of infections caused by various Candida species.